OSTEOCALCIN AND OSTEONECTIN EXPRESSION AFTER DOUBLE APPLICATION OF PLATELET-RICH PLASMA IN RABBITS - Burcu ÖZDEMİR; Bülent KURTİŞ; Gülay TÜTER; Burcu ŞENGÜVEN; Benay YILDIRIM; Gönen ÖZCAN (Istanbul University, 2016)
Purpose: Platelet-rich plasma (PRP) is a novel method for transferring autogenous growth factors to the wound area. The aim of this study was to evaluate the efficacy of double-application of PRP (DA-PRP) on bone healing in rabbit cranial defects by examining osteonectin (ON) and osteocalcin (OC) expression. Materials and Methods: Twenty-eight rabbits, each with two surgically prepared calvarial bone defects, were included in this study and divided into six groups: The defects (N=56) were treated with either a single-application of PRP (SA-PRP) (n=10), a combination of SA-PRP and betatricalciumphosphate (SA-PRP+β-TCP) (n=10), only DAPRP (n=8), both DA-PRP and beta-tricalciumphosphate (DA-PRP+β-TCP) (n=8), only beta-tricalciumphosphate (β-TCP) (n=10), or controls (n=10). The animals were sacrificed at 30th day postoperatively and samples were immunohistochemically examined for ON and OC expressions. Results: It was determined that DA-PRP did not significantly improve the ON and OC percentages achieved by SA-PRP or the controls. The three groups treated with β-TCP showed a higher percentage of ON than those treated without β-TCP (p<0.05). The β-TCP treated groups and SA-PRP group demonstrated higher OC percentage than DA-PRP and control groups (p<0.05). Conclusion: The present findings suggest that DAPRP did not have a significant effect on the healing of non-critical size rabbit cranial bone defects.